The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/107327481302000105
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Standard of Care: A Review of Novel Immunotherapy Trials for the Treatment of Lung Cancer

Abstract: Recent clinical trials in lung cancer demonstrate the potential of immunotherapeutics to increase overall survival in patients with lung cancer compared with the current standard of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 45 publications
0
42
0
6
Order By: Relevance
“…31,32 Clinical trials are underway evaluating therapeutic vaccines targeting p53 in ovarian cancer, colorectal cancer, and non-small cell lung cancer. [33][34][35][36][37] Overall, p53-specific immune responses have been observed in patients, but significant reductions in tumor burdens have not been demonstrated. It has been suggested that multiple epitope vaccines, Treg elimination, and/or CTLA-4 blockade should be assessed in combination with p53 vaccines to increase their clinical efficacy.…”
Section: P53mentioning
confidence: 99%
“…31,32 Clinical trials are underway evaluating therapeutic vaccines targeting p53 in ovarian cancer, colorectal cancer, and non-small cell lung cancer. [33][34][35][36][37] Overall, p53-specific immune responses have been observed in patients, but significant reductions in tumor burdens have not been demonstrated. It has been suggested that multiple epitope vaccines, Treg elimination, and/or CTLA-4 blockade should be assessed in combination with p53 vaccines to increase their clinical efficacy.…”
Section: P53mentioning
confidence: 99%
“…These are either monoclonal antibodies directed at the extracellular domain of the EGFR and inhibiting the binding of natural ligands to the receptor, or low molecular weight tyrosine kinase inhibitors (TKIs) that inhibit the tyrosine kinase activity of EGFR, generally by competing reversibly with ATP for the ATP binding site [26]. Targeting the EGFR with a cancer vaccine is a newly strategy currently in clinical scrutiny using the active immune deprivation of EGF ligand as important tumor growth factor (CIMAvax EGF) [27, 28]. …”
Section: Nsclc Biology and Target Antigens For Cancer Vaccinesmentioning
confidence: 99%
“…Although significant advances have been made in the treatment of NSCLC using molecular targeted therapies such as erlotinib and crizotinib, the median OS for patients with advanced NSCLC remains low (5,6), and acquired resistance to target agents is a major clinical problem. Therefore, the development of novel therapies is needed (7).…”
Section: Introductionmentioning
confidence: 99%